Anthracene and TCNQ doping of substituted nickel phthalocyanine: Effects on the electrical and optical properties of spin coated thin films - Hassan, Aseel K.; Basova, Tamara; Gürek, Ayşe Gül; Ahsen, Vefa (E D P Sciences, 2013)
In this work, we study the controlled doping of thin films of substituted nickel phthalocyanine, NiPcR8, where R=-SC6H13, with anthracene and TCNQ and investigate the effects of the extent of this doping on the optical and electrical properties of NiPcR8 films. Optical constants, namely index of refraction (n) and extinction coefficient (k) have increased for both types of doping, as determined from spectroscopic ellipsometry measurements. Conductivity is shown to increase by about four orders of magnitudes compared to pure NiPcR8 films as a result of anthracene doping while TCNQ has resulted in almost six orders of magnitudes increase in the film's conductivity.
14th International Conference on Organized Molecular Films (ICOMF) -- JUL 10-13, 2012 -- Paris, FRANCE
Keywords: Iodine